2015
DOI: 10.1016/j.lwt.2014.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of formulation and process of Australian sweet lupin (ASL)-wheat bread

Abstract: a b s t r a c tThis study aimed to optimise formulation and process factors of Australian sweet lupin (ASL)-refined wheat bread bun to maximise the ASL level whilst maintaining bread quality using response surface methodology (RSM) with a central composite face-centered design. Statistical models were generated that predicted the effects of level of ASL flour incorporation (g/100 g of ASL-wheat composite flour), ASLflour volume weighted mean particle size (mm), water incorporation level (g/100 g ASL-wheat comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Increasing amounts of lupin flour (up to 20%) decrease the bread volume and the crumb texture quality [6], but allows increasing the content in protein and dietary fiber, apart from the content of bioactive compounds like phenols and carotenoids [7]. Most of the studies reported for bread enrichment with lupin have been carried out using L. angustifolius (Blue Lupine with narrow leaves) [8] or L. albus (White Lupine) [4]; although Lupinus mutabilis Sweet shows better adaptation to poor soils and extreme conditions limited information exists about its application in breadmaking.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing amounts of lupin flour (up to 20%) decrease the bread volume and the crumb texture quality [6], but allows increasing the content in protein and dietary fiber, apart from the content of bioactive compounds like phenols and carotenoids [7]. Most of the studies reported for bread enrichment with lupin have been carried out using L. angustifolius (Blue Lupine with narrow leaves) [8] or L. albus (White Lupine) [4]; although Lupinus mutabilis Sweet shows better adaptation to poor soils and extreme conditions limited information exists about its application in breadmaking.…”
Section: Introductionmentioning
confidence: 99%
“…), the R-squared, and the adjusted R-squared. Empirical models developed were based on the general equation for second-order responses as shown in Equation ( 1), where Y, β, and X represent the predicted response, regression coefficients, and independent variable, respectively [61,62].…”
Section: Modeling Of Responsesmentioning
confidence: 99%
“…The addition of lupin to refined wheat bread reduced the glycaemic index (Hall et al, 2005), and its consumption showed reduction in obesity (Lee et al, 2006) and hypertension (Yang et al, 2010). Because of these properties, the lupin may be a potential ingredient in dietetic food products (Martinez-Villaluenga et al, 2006;Wang & Clements, 2008;Villarino et al, 2015aVillarino et al, , 2015b). Hence, it was aimed to produce novel snack/chips using different lupin flour formulations in combination with wheat and corn flours, using either whole or hulled lupin and processing of snack using different cooking methods (baking and frying) and evaluation of their effects on certain physico-chemical and sensory properties of the resulting chips.…”
Section: Introductionmentioning
confidence: 99%
“…The high nutritional value and absence of gluten also make lupin an alternative raw material for gluten-free products. Lupin is also used as soy alternative in products such as a gluten-free flour, cookies, bread, biscuits, cakes, pasta, confectionery, soy sauce, mayonnaise and as emulsifier and appetiser (M ülayim & Acar, 2008;Jayasena & Nasar-Abbas, 2011;Villarino et al, 2015aVillarino et al, , 2015b. The addition of lupin to refined wheat bread reduced the glycaemic index (Hall et al, 2005), and its consumption showed reduction in obesity (Lee et al, 2006) and hypertension (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%